Development of Protection Suits for Bloodborne Pathogen Safety for The Emergency Use During The Pandemic of COVID-19 in Thailand - Tapasa, Kanit; Tungchaiwattana, Somjit; Kamwongwian, Sompong; Thepbutdee, Suwannee (Bulletin of Applied Sciences, 2022)
During the epidemic of COVID-19 in Thailand at the beginning of 2020, there was a shortage of personal protective suit for medical personnel in Thailand as they were always imported. The department of Science Service in cooperating with other institutes developed the coverall level 4 suit, according to ANSI/AAMI PB70, for medical use. Two types of spunbond nonwoven fabric were used to tailor the the coverall Level 4 suit, namely, Polypropylene (PP) with the weight of 40 gsm and Polyethylene terephthalate (PET) 50 gsm. Both fabric were coated with the breathable Polyethylene (PE) film 20 gsm. The physical properties of both fabric is similar to the commercial coverall suits. Both fabric could prevent the penetration of Phi-X174 bacteriophage, that used as the phage suspension which had a spherical shape with 0.027 mm in diameter and smaller than COVID-19 disease (0.125 mm in diameter). Seaming is also an important factor because seams must prevent the virus penetration. It was found that ultrasonic seaming was the best method. The usability survey indicated that the medical staffs satisfied with the coverall Level 4 suits as they was suitable and flexible to use. Nevertheless, the PET fabric was more preferred than the PP.